AB0520 Mortality in Systemic Lupus Erythematosus in A Argentinian Cohort. (15th July 2016) - Juarez, V.; Aciar, M.; Cucchiaro, N.; Rojas Tessel, R.; Picco, E.; Buschiazzo, E.; Lencina, M.V.; Aciar, M.D.L.A.; Artes Rocha, I.; Crespo Espindola, M.E.
Abstract : Background: Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disease associated with a high morbidity and mortality. The specific causes of death may vary among ethnic groups. Objectives: To examine mortality rates related to SLE in a single Argentinian population. Methods: A retrospective cohort study was designed. Clinical Record of SLE patients treated between 2000 and 2005 and followed until 2015 in a tertiary no academical hospital that does not attend pediatric population were reviewed, including demografic and clinical data. The cause of death was searched from the medical records and deaths certificates from the Public Health Archives. Continuous data was expressed in median and interquartile range (IQR), categorical data in frequency and percentage. Chi-square test or Fisher's test was used to analyse categorical data and Mann-Whitney or Student's T-Test for continuous data. Kaplan – Meier survival curves were calculated. A p value <0.05 was considered as significant. Results: Fifty- five patients were enrolled, 48 women (87%), with a median age of 37 years (IQR:29–44.5), median disease duration of 9 years (IQR:3–12.3) and a total follow-up of 500 patients- years.Thirty- five patients (63%) were diagnoses after the first visit. Two (3.6%) were smokers, 16 (29.1%) had hypertension, 8 (14%) were diabetics and 9 (16.7%) has dyslipidemia. Treatments included glucocorticoids (>10 mg/ day of prednisone) in 47 (85%), immunosuppressive therapy 27 (49.1%) and anti-malarial 44 (80%). Renal involvement was found in 30 (54%) patients. Conclusions: Long-term survival in a single center of SLE argentinian patients was low in comparation with oteher studies. An cumulative survival from diagnosis of 81% at 5 years and 61% at 10 years was observed. Infection and SLE activity were the main causes of death Disclosure of Interest: None declared